Morphological evaluation of atrioventricular septal defects by magnetic resonance imaging. Issue 2 (August 1990) - Parsons, J M; Baker, E J; Anderson, R H; Ladusans, E J; Hayes, A; Qureshi, S A; Deverall, P B; Fagg, N; Cook, A; Maisey, M N
Abstract : Twelve patients aged between 2 weeks and 22 months (median 6 weeks) with atrioventricular septal defects were examined with a 1.5 T, whole body, magnetic resonance imaging system. Ten patients had a common atrioventricular orifice (complete defect) while two patients had separate right and left valve orifices (partial defect). Associated cardiac malformations included the tetralogy of Fallot in two, isomerism of the right atrial appendages and pulmonary atresia in two, and right isomerism and double outlet right ventricle in one. All had previously been examined by cross sectional echocardiography. Eight subsequently had angiography and six underwent surgical correction. There was one operative death and three other deaths. Three of these patients underwent postmortem examinations. Small children and infants were scanned inside a 32 cm diameter head coil. Multiple electrocardiographically gated sections 5 mm thick, separated by 0.5 mm, were acquired using a spin echo sequence with echo time of 30 ms. A combination of standard and oblique imaging planes was used. Magnetic resonance imaging was more accurate than echocardiography in predicting the size of the ventricular component of the defect. It was also better than either echocardiography and angiography in identifying the presence of ventricular hypoplasia. All these findings were confirmed by surgical or postmortem examinations or both. Magnetic resonance imaging is capable of providing detailed morphological information in children with atrioventricular septal defects which is likely to be of value in their management.